Metabolic engineering of proanthocyanidin production by repressing the isoflavone pathways and redirecting anthocyanidin precursor flux in legume. Issue 7 (24th January 2016) - Li, Penghui; Dong, Qiang; Ge, Shujun; He, Xianzhi; Verdier, Jerome; Li, Dongqin; Zhao, Jian
Summary: MtPAR is a proanthocyanidin (PA) biosynthesis regulator; the mechanism underlying its promotion of PA biosynthesis is not fully understood. Here, we showed that MtPAR promotes PA production by a direct repression of biosynthesis of isoflavones, the major flavonoids in legume, and by redirecting immediate precursors, such as anthocyanidins, flux into PA pathway. Ectopic expression of MtPAR repressed isoflavonoid production by directly binding and suppressing isoflavone biosynthetic genes such as isoflavone synthase ( IFS ). Meanwhile, MtPAR up‐regulated PA‐specific genes and decreased the anthocyanin levels without altering the expression of anthocyanin biosynthetic genes. MtPAR may shift the anthocyanidin precursor flux from anthocyanin pathway to PA biosynthesis. MtPAR complemented PA‐deficient phenotype of Arabidopsis tt2 mutant seeds, demonstrating their similar action on PA production. We showed the direct interactions between MtPAR, MtTT8 and MtWD40‐1 proteins from Medicago truncatula and Glycine max, to form a ternary complex to trans ‐activate PA‐specific ANR gene. Finally, MtPAR expression in alfalfa ( Medicago sativa ) hairy roots and whole plants only promoted the production of small amount of PAs, which was significantly enhanced by co‐expression of MtPAR and MtLAP1 . Transcriptomic and metabolite profiling showed an additive effect between MtPAR and MtLAP1 on the production of PAs, supporting that efficient PA production requires more anthocyanidin precursors. This study provides new insights into the role and mechanism of MtPAR in partitioning precursors from isoflavone and anthocyanin pathways into PA pathways for a specific promotion of PA production. Based on this, a strategy by combining MtPAR and MtLAP1 co‐expression to effectively improve metabolic engineering performance of PA production in legume forage was developed.